Introduction to the special issue on 'global trading system and protectionism: China, the United States and Europe'. Issue 4 (2nd October 2019) - Fung, K. C.; Fu, Xiaolan; Zheng, Jinghai
ABSTRACT: In this Introduction to our Special Issue, we provide detailed and critical comments and summaries of the excellent papers. The papers are important contributions to the China-U.S. and China-Europe economic and trade issues in the context of the global trading environment, as shaped by the current unorthodox policies of the Trump Administration. The wonderful papers dealt with relevant issues related to international trade, investment, national security, trade laws, intellectual property rights laws, political science, business, etc. They constitute a must-read for academics, policy and business researchers, think tank fellows, experts in international organizations, as well as government-related researchers in various national capitals. The three Co-editors are all experienced and accomplished academics with vast experiences in public policies. As academics, they may hold different views but their unique and diverse perspectives provide an important background to the Special Issue. They jointly contributed major efforts to this timely and important Special Issue.